Body of Knowledge: Using Prosections to Teach Pelvic Anatomy in OBGYN Residency. (October 2016) - Lane, Andrew; Williams, Shanna; Keiser, Sharon; Elder, Jeffrey
Abstract : BACKGROUND: As residency programs update curricula, lab-based anatomic education is often abandoned due to high costs and time constraints. This has led to a new generation of residents with a knowledge deficit in surgical anatomy. METHODS: All residents took baseline written and practical examinations and were then randomized into two groups within PGY levels. Both groups completed a self-directed reading assignment. The intervention group received an additional one-hour structured review of pelvic anatomy using fresh, cadaveric prosections. Both groups then completed post-intervention examinations. RESULTS: Fifteen out of 23 residents completed the study. The intervention group showed a significant improvement in practical exam scores over the control group ( P ⩽.01), but not on written ( P =.7) or combined scores ( P =.052). The intervention group showed significant improvements in combined ( P =.049), and practical ( P ⩽.01) scores. DISCUSSION: We demonstrated the ability of a straightforward educational intervention to impact anatomic practical exam performance. We also showed that all residents benefited from an anatomy review. This study is important in its comparison of two modalities of resident anatomic education. The utilization of a single guided prosection session provided a measurable benefit. Additionally, the simple act of anatomic self-study was beneficial as well and should not be overlooked in our resource intensive age.